Knee joint loading at the inside and outside leg in alpine skiing: a comparison between carved and skidded turns - Klous, M.; Müller, E.; Schwameder, H. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In recreational skiing, 40-64% of all injuries occur at the lower extremities, predominately at the knee (31%) (Klous, 2007). These high percentages clearly show the need for systematic research to determine joint loading on the lower extremities in skiing. So far, only rough estimations of joint loading in skiing are reported (Quinn & Mote, 1992). The present study is part of a larger project in which 3D joint loading on the lower extremities in carved and skidded ski and snowboard turns were determined using inverse dynamics. The purpose of the present study is to compare knee joint loading at the inside and outside leg in carved and skidded ski turns. It is supposed that knee joint loading is higher in carving than in skidding.